El rol del ejecutivo en la producción normativa: el Ecuador entre 1979 y 2016 - Santiago Llanos Escobar; Wladimir García Vinueza (Ius Humani. Jornal do direito, 2018)
This work is based on the following research question: how the executive has gotten to approve his bills in the legislative? To carry out this analysis, Ecuador is taken as a case study between 1979 and 2016, starting from the return to democracy. For this purpose, through a quantitative methodological proposal using descriptive statistics, it is intended to review the ways in which each of the Ecuadorian executives has used his legislative initiative, emphasizing the conditions present in each of their governments for this effect. Therefore, from the collection and systematization of information available in official media, the ways in which each executive has submitted their bills to the legislature are reviewed, evidencing clear patterns which determine why executives get to approve their bills. The study establishes conclusions based on the functioning of the legislative executive relationship in Ecuador; proposes an agenda that allows to determine the causal elements that help an executive to increase his level of legislative success.